Human-Environment Interactions
XXX, 406 p.
Keywords: Human-environment interaction (HEI) provides a framework that brings together scholarship sharing both disciplinary depth and interdisciplinary scope to examine past, present, and future social and environmental change in different parts of the world. This volume brings senior and junior scholars together, and in so doing connects these historically influential traditions to new and cutting-edge approaches that give us a glimpse into current and future trends in interdisciplinary science of human-environment interaction. The volume offers a microcosm of contemporary HEI research in terms of thematic, theory and methodology, level of analysis, and regional coverage. Drawing on research from eleven countries across four continents, the 16 chapters in the volume bring perspectives from various specialties in anthropology and human ecology, institutional analysis, historical and political ecology, geography, archaeology, and land change sciences. The four sections of the volume reflect complementary approaches to HEI: health and adaptation approaches, land change and landscape management approaches, institutional and political-ecology approaches, and historical and archaeological approaches.